2015
DOI: 10.1097/md.0000000000001987
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Intra-abdominal Sepsis, Not Penetrating Behavior Itself, Is Associated With Worse Postoperative Outcome After Bowel Resection for Crohn Disease

Abstract: It is generally believed that penetrating behavior is associated with worse surgical outcomes in Crohn disease (CD). We hypothesized that intra-abdominal sepsis (IAS), but not penetrating behavior itself, contributes to postoperative morbidity in patients undergoing bowel resection for CD.Patients who underwent surgery from April 2010 to April 2014 were retrospectively identified from a prospectively maintained database. Demographic information and preoperative and operative data were collected. The outcomes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…A preoperative lag allowed for amelioration of patient conditions – reducing the inflammatory environment [58-60], increasing serum albumin [59, 60], weaning or suspending CST therapy [57, 59], and treating abscesses [59, 60] – as opposed to patients operated on immediately [58, 59]. These properties have also been attributed to nutritional support, both enteral and parenteral, by other authors [44, 47, 48, 50, 52-54, 69-72]. Also, in one of the reviewed studies [59], going straight to surgery (non-EEN patients) was an independent risk factor for anastomotic leaks and/or intra-abdominal abscesses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A preoperative lag allowed for amelioration of patient conditions – reducing the inflammatory environment [58-60], increasing serum albumin [59, 60], weaning or suspending CST therapy [57, 59], and treating abscesses [59, 60] – as opposed to patients operated on immediately [58, 59]. These properties have also been attributed to nutritional support, both enteral and parenteral, by other authors [44, 47, 48, 50, 52-54, 69-72]. Also, in one of the reviewed studies [59], going straight to surgery (non-EEN patients) was an independent risk factor for anastomotic leaks and/or intra-abdominal abscesses.…”
Section: Discussionmentioning
confidence: 99%
“…Although EN is not indicated as treatment for CD in adults by Chinese guidelines [62], eight of the excluded studies originated from China. The article by Li et al [57] was produced by the same institution as that of seven [46-48, 50-52, 54] of the previous 8 studies, the latter being well known for its publications regarding this topic [31, 34, 63]. One of the excluded articles is Japanese [45].…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative PLR and NLR are simply, inexpensively and widely available markers to reflect systemic inflammation status [ 10 , 17 , 18 ]. Several recent studies have demonstrated that preoperative inflammation state is associated with a worse postoperative outcome after surgery [ 19 21 ]. Our study showed that both preoperative PLR and NLR have a positive correlation with the PPCs particularly pneumonia and atelectasis in NSCLC patients undergoing radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the incidence of severe sepsis is estimated to be 300 cases per 100,000 of the population, and the age-adjusted mortality caused by sepsis is >60 per 100,000 (6). Sepsis is associated with gastrointestinal tract dysfunction, manifesting as dysfunction in gastrointestinal motility, nutritional absorption and the intestinal immunological barrier, which ultimately results in intestinal mucosa atrophy, dysbacteriosis and enterogenic infection, thereby causing or aggravating dysfunction in other organs (7,8). Hiltebrand et al (9) reported that stomach blood flow was reduced by 55% in a sepsis model in pigs.…”
Section: Introductionmentioning
confidence: 99%